Cretaceous to Middle Cenozoic Exhumation History of the Cordillera de Domeyko and Salar de Atacama Basin, Northern Chile. Issue 2 (1st February 2019) - Henriquez, Susana; DeCelles, Peter G.; Carrapa, Barbara
Abstract: Spatiotemporal patterns of deformation and exhumation in the central Andes are key parameters for reconstructing the kinematic history of the orogenic belt. Previous studies of the retroarc thrust belt document overall eastward propagation of deformation since the late Eocene, but the amount and timing of exhumation during the early phase of Andean orogeny remains largely unconstrained, particularly in the modern forearc region. In order to determine the timing and amount of exhumation prior to the late Eocene, we employed a multidating approach combining zircon U‐Pb geochronology with apatite fission track and apatite (U‐Th)/He thermochronology. We focus on the low‐temperature cooling history of the Cordillera de Domeyko thrust belt and synorogenic deposits in the Salar de Atacama basin. Our results show Late Cretaceous to Oligocene cooling and exhumation in the Cordillera de Domeyko. The distribution of cooling ages in the forearc indicates three periods of exhumation: 86–65, 65–50, and 50–28 Ma. The amount of cooling was variable in space and time but requires total exhumation of 2.5–3.3 km of rocks above major structures in the thrust belt. Regional unconformities in the Salar de Atacama basin correlate with periods of eastward migration of the orogenic front at 65 Ma and 50–40 Ma. Pulses of deformation at the front of the thrust belt alternated with periods of out‐of‐sequence hinterland deformation and exhumation. Overall, our data show that shortening in the central Andes commenced during the Late Cretaceous (as early as 86 Ma) and that deformation (shortening) and exhumation were coupled in space and time. Key Points: The Cordillera de Domeyko experienced exhumation during the upper Cretaceous, Paleocene, Eocene, and Oligocene The Cordillera de Domeyko experienced 2.5‐3.3 km of exhumation above major structures Regional unconformities in the Salar de Atacama basin correspond to periods of migration of the orogenic front at 65 and between 40 and 50 Ma